2007
DOI: 10.1074/jbc.m703962200
|View full text |Cite
|
Sign up to set email alerts
|

Translation Elongation Factor eEF1A2 Is Essential for Post-weaning Survival in Mice

Abstract: Translation elongation factor eEF1A, formerly known as EF-1␣, exists as two variant forms; eEF1A1, which is almost ubiquitously expressed, and eEF1A2, whose expression is restricted to muscle and brain at the level of whole tissues. Expression analysis of these genes has been complicated by a general lack of availability of antibodies that specifically recognize each variant form. Wasted mice (wst/wst) have a 15.8-kilobase deletion that abolishes activity of eEF1A2, but before this study it was unknown whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 42 publications
(39 reference statements)
2
86
0
2
Order By: Relevance
“…In recent years, two lines of evidence have implicated eEF1A2 in disease, suggesting that there may indeed be subtle differences in the functions of the two forms of eEF1A. First, EEF1A2 has been shown to be a potential oncogene; it is overexpressed in a proportion of ovarian tumors but is not expressed in normal ovary (51), and it is similarly overexpressed in two-thirds of breast tumors but not normal breast tissue (52,53). Phosphorylation has been determined to modify some of the activities of mammalian eEF1A, typically resulting in a stimulatory effect (32,54).…”
Section: Fig 6 Mutation On Sermentioning
confidence: 99%
“…In recent years, two lines of evidence have implicated eEF1A2 in disease, suggesting that there may indeed be subtle differences in the functions of the two forms of eEF1A. First, EEF1A2 has been shown to be a potential oncogene; it is overexpressed in a proportion of ovarian tumors but is not expressed in normal ovary (51), and it is similarly overexpressed in two-thirds of breast tumors but not normal breast tissue (52,53). Phosphorylation has been determined to modify some of the activities of mammalian eEF1A, typically resulting in a stimulatory effect (32,54).…”
Section: Fig 6 Mutation On Sermentioning
confidence: 99%
“…eEF1A1 is almost ubiquitously expressed, while eEF1A2 is normally expressed only in the heart, muscles, brain (13)(14)(15)(16), pancreatic islet cells, and enteroendocrine cells in colon crypts (16). During postnatal development, a transition from eEF1A1 to eEF1A2 occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The near-ubiquitous form, eEF1A1, is expressed in all tissues throughout development but is absent in adult muscle and heart, which express eEF1A2 instead (68,69) . eEF1A2 is also found in some other cell types, including large motor neurons, islet cells in the pancreas and enteroendocrine cells in the gut (70,71) . We showed that in H1355, treatment with IFN α increased both eEF1A1 and eEF1A2 expression, but to different degrees and with different kinetics.…”
Section: Raf Kinases and Protein Synthesis Machinerymentioning
confidence: 99%